Artificial Solar Tree-Based Smart Street Lighting System with Adaptive Illumination and IOT Integration (International Journal of Scientific Research in Science and Technology, 2025)
As renewable energy solution demands increase, there is a need for novel urban infrastructure towards sustainability. An Artificial Solar Tree in this paper brings together diverse functionalities to facilitate efficiency in energy as well as ecological consciousness. The system uses eight solar panels within a neat, tree-structured layout in an effort to harness solar power as much as possible while still consuming less space. A 60-second timed charging point, regulated by an LCD countdown timer, offers short-term charging for handheld devices, ensuring equitable and effective energy distribution. A real-time pollution monitoring system also detects and shows oxygen levels on an LCD display, providing useful air quality information. The system is automated with Arduino, IR sensors, and LDR sensors, which dynamically control streetlight intensity according to ambient light and pedestrian traffic. Experimental analysis reveals substantial energy saving, effective resource use, and improved environmental monitoring. The designed system is a space-saving, multifunctional solution for cities, supporting sustainable energy consumption and public awareness of environmental conditions.
Keywords: Space optimization; Timed charging point; LCD countdown timer; Handheld device charging; Pollution monitoring system; Oxygen level detection; Air quality information; Arduino automation; IR sensors; LDR sensors; Streetlight intensity control; Ambient light detection; Pedestrian traffic sensing